ITGB3 promotes cisplatin resistance in osteosarcoma tumors. (11th February 2023) - Li, Qian; Chen, Guangyou; Jiang, Huachai; Dai, Haoping; Li, Dongdong; Zhu, Kai; Zhang, Kaiquan; Shen, Huarui; Xu, Houping; Li, Sen
Abstract: Objective: Osteosarcoma is the most malignant and common primary bone tumor with a high rate of recurrence that mainly occurs in children and young adults. Therefore, it is vital to facilitate the development of novel effective therapeutic means and improve the overall prognosis of osteosarcoma patients via a deeper understanding of the mechanisms of chemoresistance in osteosarcoma progression. Methods: In this research, the relationship between ITGB3 and the clinical characteristics of patients was detected through analysis of publicly available clinical datasets. The expression of ITGB3 was analysis in collected human osteosarcoma tissues. In addition, the potential functions of ITGB3 in the cisplatin resistance of osteosarcoma cells were investigated in vitro and in tumor xenotransplantation. Finally, the molecular mechanism of ITGB3 in the progression and recurrence of osteosarcoma were explored via transcriptome analysis. Results: ITGB3 was identified as a potential regulator of tumorigenicity and cisplatin resistance in relapsed osteosarcoma. Furthermore, the decreased osteosarcoma cell proliferation and migration ability in ITGB3 knockout osteosarcoma cells were related to increased apoptosis and slowing cell cycle progression. In addition, ITGB3 had a positive correlation with cisplatin resistance in cells and tumor xenografts in mice. Accordingly, ITGB3 performed the functions of proliferation and cisplatin resistance in osteosarcoma through the MAPK and VEGF signaling pathways. Conclusion: Our results will contribute to a better understanding of the function and mechanism of ITGB3 in osteosarcoma cisplatin resistance and provide a novel therapeutic target to decrease cisplatin resistance and tumor recurrence in osteosarcoma patients. Abstract : In the present work, ITGB3 knockout osteosarcoma cells had the decreased proliferation and migration ability, increased apoptosis and slowing cell cycle progression in vitro, and reduced cisplatin resistance in vivo. Further analyses suggested that MAPK and VEGF signaling pathways may involved in these process.